Assessment of stationarity of annual and seasonal river flow in the Upper Ob basin - Svetlana Y. Samoilova; Olga V. Lovtskaya; Anastasia B. Golubeva (Водное хозяйство России: проблемы, технологии, управление)
Th e climate-induced changes recorded in the recent decades in water regime of Russian rivers make the study topical. Th is is associated with breaks in the homogeneity of runoff series and requires a revision of existing methods for hydrological calculations and forecasts. In this work, a statistical analysis of series of average annual and average seasonal fl ows for the rivers of the Upper Ob basin (up to the Novosibirsk reservoir) has been performed.